2015
DOI: 10.1371/journal.pone.0119348
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipocytes Stimulate Invasion of Breast Cancer MCF-7 Cells by Secreting IGFBP-2

Abstract: Background and AimsA better understanding of the effects of human adipocytes on breast cancer cells may lead to the development of new treatment strategies. We explored the effects of adipocytes on the migration and invasion of breast cancer cells both in vitro and in vivo.MethodsTo study the reciprocal effects of adipocytes and cancer cells, we co-cultured human mature adipocytes and breast cancer cells in a system devoid of heterogeneous cell-cell contact. To analyze the factors that were secreted from adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 32 publications
5
62
0
Order By: Relevance
“…Breast cancer cells exposed to adipocyte conditioned media, or in co-culture with adipocytes, have previously been shown to have modified proliferation, migration, and invasion [9, 12, 13, 46, 4952]. Similar effects have been observed in 3-D cultures [53, 54] and xenograft models [13, 55].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Breast cancer cells exposed to adipocyte conditioned media, or in co-culture with adipocytes, have previously been shown to have modified proliferation, migration, and invasion [9, 12, 13, 46, 4952]. Similar effects have been observed in 3-D cultures [53, 54] and xenograft models [13, 55].…”
Section: Discussionmentioning
confidence: 71%
“…Several studies have shown the role of endocrine and paracrine signaling mechanisms in driving adipocyte-cancer cell crosstalk [9, 12, 13]. We next sought to address the possibility that adipocyte-derived fatty acids could act as a metabolic stimulus on breast cancer cell proliferation and migration in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the breast tumor microenvironment, adipocytes have been reported to produce a number of biologically active compounds including different cytokines, e.g., MMP-11, plasminogen activator inhibitor-1 (PAI-1), collagen VI, IL-1β, IL-6, tumor necrosis factor – α (TNF-α), insulin-like growth factor-I (IGF-I), and leptin; many of which are metastasis-associated proteins [3436]. In particular, Wolfson et al suggested that leptin has a key effect on breast cancer; and in adipocyte-adjacent breast cancer cells, due to stimulation of various regulatory pathways such as Notch, Wnt and Nanog signaling axis [37].…”
Section: Obesity-related Microenvironment and Its Influence On Tummentioning
confidence: 99%
“…targeted therapies such as tamoxifen, traztuzimab), an understanding of the crosstalk between cancer and non-cancer cells has proved to be less forthcoming in part because of limited models that allow dissection of the individual contributions of a complex cellular milieu. Simple co-culture models have been successfully implemented to identify factors mediating interactions between cancer and stromal compartments and point toward phenotypic changes that occur as a result (Wang et al 2015; Furukawa et al 2015; Wan et al 2014; Hollmén et al 2015; Rozenchan et al 2009; Straussman et al 2012). However, more complex in vitro models incorporating aspects of the microenvironment such as dimensionality (Weigelt et al 2014; Thoma et al 2014; Sung et al 2013; Krishnan et al 2011; Bin Kim et al 2004) and structure (Bischel et al 2015; Pisano et al 2015; Zervantonakis et al 2012; Choi et al 2015) have more successfully recreated functional responses of breast cancer seen in vivo .…”
Section: Introductionmentioning
confidence: 99%